Is it me? The impact of patient–physician interactions on lupus patients' psychological well-being, cognition and health-care-seeking behaviour. Issue 2 (22nd July 2020) - Sloan, Melanie; Naughton, Felix; Harwood, Rupert; Lever, Elliott; D'Cruz, David; Sutton, Stephen; Walia, Chanpreet; Howard, Paul; Gordon, Caroline
Abstract: Objective: The aim was to explore the impact of patient–physician interactions, pre- and post-diagnosis, on lupus and UCTD patients' psychological well-being, cognition and health-care-seeking behaviour. Methods: Participants were purposively sampled from the 233 responses to a survey on patient experiences of medical support. Twenty-one semi-structured interviews were conducted and themes generated using thematic analysis. Results: The study identified six principal themes: (i) the impact of the diagnostic journey; (ii) the influence of key physician(s) on patient trust and security, with most participants reporting at least one positive medical relationship; (iii) disparities in patient–physician priorities, with patients desiring more support with quality-of-life concerns; (iv) persisting insecurity and distrust, which was prevalent and largely influenced by previous and anticipated disproportionate (often perceived as dismissive) physician responses to symptoms and experiences of widespread inadequate physician knowledge of systemic autoimmune diseases; (v) changes to health-care-seeking behaviours, such as curtailing help-seeking or under-reporting symptoms; and (vi) empowerment, including shared medical decision-making and knowledge acquisition, which can mitigate insecurity and improve care. Conclusion: Negative medical interactions pre- and post-diagnosis can cause a loss of self-confidence and a loss of confidence and trust in the medical profession. This insecurity can persist even in subsequent positive medical relationships and should be addressed. Key physicians implementing empowering and security-inducing strategies, including being available in times of health crises and validating patient-reported symptoms, might lead to more trusting medical relationships and positive health-care-seeking behaviour.